The tropical tropopause inversion layer: variability and modulation by equatorial waves - R. Pilch Kedzierski; K. Matthes; K. Matthes; K. Bumke (Atmospheric Chemistry and Physics, 2016)
The tropical tropopause layer (TTL) acts as a transition layer between the troposphere and the stratosphere over several kilometers, where air has both tropospheric and stratospheric properties. Within this region, a fine-scale feature is located: the tropopause inversion layer (TIL), which consists of a sharp temperature inversion at the tropopause and the corresponding high static stability values right above, which theoretically affect the dispersion relations of atmospheric waves like Rossby or inertia–gravity waves and hamper stratosphere–troposphere exchange (STE). Therefore, the TIL receives increasing attention from the scientific community, mainly in the extratropics so far. Our goal is to give a detailed picture of the properties, variability and forcings of the tropical TIL, with special emphasis on small-scale equatorial waves and the quasi-biennial oscillation (QBO). We use high-resolution temperature profiles from the COSMIC satellite mission, i.e., ∼ 2000 measurements per day globally, between 2007 and 2013, to derive TIL properties and to study the fine-scale structures of static stability in the tropics. The situation at near tropopause level is described by the 100 hPa horizontal wind divergence fields, and the vertical structure of the QBO is provided by the equatorial winds at all levels, both from the ERA-Interim reanalysis. We describe a new feature of the equatorial static stability profile: a secondary stability maximum below the zero wind line within the easterly QBO wind regime at about 20–25 km altitude, which is forced by the descending westerly QBO phase and gives a double-TIL-like structure. In the lowermost stratosphere, the TIL is stronger with westerly winds. We provide the first evidence of a relationship between the tropical TIL strength and near-tropopause divergence, with stronger (weaker) TIL with near-tropopause divergent (convergent) flow, a relationship analogous to that of TIL strength with relative vorticity in the extratropics. To elucidate possible enhancing mechanisms of the tropical TIL, we quantify the signature of the different equatorial waves on the vertical structure of static stability in the tropics. All waves show, on average, maximum cold anomalies at the thermal tropopause, warm anomalies above and a net TIL enhancement close to the tropopause. The main drivers are Kelvin, inertia–gravity and Rossby waves. We suggest that a similar wave modulation will exist at mid- and polar latitudes from the extratropical wave modes.